Criminal Actions Against People Exploiting Children In Accordance To Indonesian Criminal Law - M. Junaeddy; Budi Parmono; Hanafi Arief (International Journal of Law, Environment, and Natural Resources, 2022)
Exploitation of children is now more widespread, not carried out by families but also by small to large institutional groups. The perpetrators are sometimes the parents themselves with the intention of making a profit. The purpose of this study is to describe the position of children in Indonesian criminal law and to analyze criminal sanctions for child exploitation. As normative legal research, this study examines laws and regulations related to child exploitation and criminal sanctions. Research results: Article 45 of the Criminal Code defines a child as an immature person if he is not yet 16 years old. Criminal law has positioned children as legal subjects who must protect themselves and their interests as well as the special rights of the state. Economic, social and sexual exploitation of children with the intention of benefiting oneself or others is a criminal act. Criminal sanctions for those who commit, order to do, and those who participate in committing the act; give or promise something by abusing power or dignity, by violence, threats or misdirection, or by giving opportunities, means or information, encouraging other people to take action; intercourse (not the wife) is punishable by imprisonment for a maximum of nine years